From hear to there. Sound and the congnitive construction of world in popular audioplays - Wißmann, Torsten; Zimmermann, Stefan (ERDKUNDE, 2010)
Mass media frequently makes use of more than visuality. With the exception of music, however, media geographers have largely ignored audio media despite its major impact on shaping and characterizing our experience of the world. We address this lacuna by exploring the world’s most successful audioplay series, “The Three Investigators”. Our approach is informed by Schafer’s acoustic ecology, which suggests soundscapes are made legible through keynote, signal and soundmark. We find additional key sound events for the creation of soundscapes in “The Three Investigators” are the storyteller, dialogue and soundframe. Using content analysis and results from an audio-integrated online survey, we examine how the everyday world can be both generated and generalized, and, explore the reception and effectiveness of this popular cultural medium. Due to the audioplay’s locus within the detective story genre, five settings or places of action are identified – independent location, headquarters, place of solution, and scene of discovery or consecutive place of discovery. These settings are signified through the presence, absence or synchronicity of specific sound events. We find that the structure of the sounds and noise must be understandable to the listener because it is his ability to associate sounds with certain types of settings that enables him to complete background noise with his imagination. Simplified sounds may even increase auditory legibility if they can be connected to the listener’s cognitive structure. Indeed, a drastically reduced representation based on generalized sound events likely facilitates the understanding of narrative content and therefore, the world itself.